2010
DOI: 10.4236/as.2010.11003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different priming treatments and priming durations on germination percentage of parsley (Petroselinum crispum L.) seeds

Abstract: The effects of different priming treatments and priming durations on germination percentage at different temperatures in parsley seeds were studied. The seeds were treated for 2, 4, 6 and 8 days with the PEG 6000 (–0.5 MPa, –1.0 MPa and –1.5 MPa), KNO3 (0.30 mol/L and 0.35 mol/L), Mannitol (0.50 mol/L and 0.60 mol/L) and hydropriming (12h, 24h, 36h and 48h) and unprimed (control). Germination studies were made at 5, 10, 15, 20 and 25°C. Percentage of germination at different temperatures was significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…Cabe ainda destacar que, mesmo no tratamento testemunha, os valores de germinação foram de 51 e 66%, para cultivares crespa e lisa, respectivamente, valor relativamente baixo. Contudo, para essa espécie, em função da sua dificuldade de germinação, tal valores são frequentemente relatados, como por exemplo nas pesquisas de Khan et al (2017), Oliveira et al (2013) e Dursun & Ekinci (2010), em que as médias foram 70%, 62% e 50,9%, respectivamente. Em relação às plântulas anormais, houve um elevado percentual para o cultivar lisa (figura 3D), mesmo na condição ideal de temperatura (20ºC), indicando baixo potencial fisiológico das sementes.…”
Section: Resultsunclassified
“…Cabe ainda destacar que, mesmo no tratamento testemunha, os valores de germinação foram de 51 e 66%, para cultivares crespa e lisa, respectivamente, valor relativamente baixo. Contudo, para essa espécie, em função da sua dificuldade de germinação, tal valores são frequentemente relatados, como por exemplo nas pesquisas de Khan et al (2017), Oliveira et al (2013) e Dursun & Ekinci (2010), em que as médias foram 70%, 62% e 50,9%, respectivamente. Em relação às plântulas anormais, houve um elevado percentual para o cultivar lisa (figura 3D), mesmo na condição ideal de temperatura (20ºC), indicando baixo potencial fisiológico das sementes.…”
Section: Resultsunclassified
“…hydropriming, osmopriming, solid matrix prim-ing can be used. Priming includes pre-sowing of seeds at controlled hydration followed by their incubation, which results in pre-germinative metabolic activation to the degree not allowing the radicle to protrude through the seed coat (Nascimento & Aragao 2004;Dursun & Ekinci 2010). In order to evaluate seed ability for germination, different methods were applied, as automatic evaluation of germination based on the automated germination scoring system (the image analysis) (Joosen et al 2010) or evaluation of glowing of substances emitted by seeds such as sinapine in cabbage (Taylor et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) has been used frequently in plant water deficit studies to induce dehydration by decreasing water potential 12 . It is observed that priming with PEG can shorten the time to seed emergence and increases the germination percentage 13 , and improves salt tolerance 14 . Moreover, seed priming with PEG enhances the chilling tolerance 15 .…”
mentioning
confidence: 99%